Visual Word Recognition Without Central Attention: Evidence for Greater Automaticity With Advancing Age. - Lien, Mei-Ching; Ruthruff, Eric; McCann, Robert S. (Psychology & Aging, 2006)
The present experiments examined the automaticity of word recognition. The authors examined whether people can recognize words while central attention is devoted to another task and how this ability changes across the life span. In Experiment 1, a lexical decision Task 2 was combined with either an auditory or a visual Task 1. Regardless of the Task 1 modality, Task 2 word recognition proceeded in parallel with Task 1 central operations for older adults but not for younger adults. This is a rare example of improved cognitive processing with advancing age. When Task 2 was nonlexical (Experiment 2), however, there was no evidence for greater parallel processing for older adults. Thus, the processing advantage appears to be restricted to lexical processes. The authors conclude that greater cumulative experience with lexical processing leads to greater automaticity, allowing older adults to more efficiently perform this stage in parallel with another task. Reprinted by permission of the publisher.